THE NATURE OF THE WORK OF THE ESTATE REGISTRAR AND HIS JURISDICTION - Baraka Karim Mahdi; Dr. Zeina Qudra Lateef (Scholar Express Journals, 2022)
In this research, we explained the nature of the work of the estate Registrar and his Jurisdiction, as his work is considered a public employee in the State, and thus the State is responsible for him as one of its followers and as a result the State is held accountable for all that is issued by the estate Registrar within the framework of his functional work, in addition to his personal accountability, or as a free practitioner, through his registration of real estate transactions and transactions, and thus he is the only responsible for his work, there is no responsibility of the State for this, Or there may be a partnership between what is an employee of the state and that he practices a free profession, but under the control and guidance of the state, that is, it has the authority to direct and control him in his registration of real estate transactions, so that the state is responsible for what is issued from him within his work of employment, being that it has authority over him, also he is responsible to others for what comes from him, while the competence of his work is exercised during a certain time, place and authority must be adhered to. By it, and therefore any conduct outside the scope of his specified jurisdiction shall be considered an infringement by the estate Registrar of his competence, and therefore there is no effect and no existence of the actions he registers within his violation of his competence at that time
Keywords: Estate Registrar; Employee; Self-Employment; Qualitative Jurisdiction